A meta‐analysis of neonatal outcomes in pregnant women with immune thrombocytopenic purpura. Issue 9 (16th June 2021) - Luo, Hongqiang; Li, Dan; Gao, Feidan; Hong, Pan; Feng, Weiying
Abstract: Aim: Thrombocytopenia is an autoimmune disorder characterized by reduced platelet counts. Neonatal thrombocytopenia incidence has been linked with immune thrombocytopenic purpura in mothers during pregnancy, possibly because antiplatelet antibodies can cross the placental barrier. To date, no study has attempted to evaluate the actual prevalence of neonatal thrombocytopenia in infants born to mothers with immune thrombocytopenic purpura. In this meta‐analysis of the available literature, we attempt to fill this gap. We want to evaluate the overall prevalence of neonatal thrombocytopenia, its severity, and the incidence of hemorrhage in infants with thrombocytopenia born from mothers with immune thrombocytopenic purpura. Methods: Adhering to PRISMA guidelines, we systematically scanned four academic databases including EMBASE, CENTRAL, Scopus, and MEDLINE to identify relevant literature. We performed a meta‐analysis to summarize thrombocytopenia incidence rate and severity in newborn infants of mothers with immune thrombocytopenic purpura. Results: We identified 21 eligible studies involving 1951 mothers and 1844 neonates. Meta‐analysis showed high prevalence for neonatal thrombocytopenia (24%). Within these, severe cases were the most prevalent (41.2%), followed by moderate (37.7%) and mild (17.6%) cases. Hemorrhage was only reported in 4.1% of the observed neonatal thrombocytopenia cases. Conclusion: This review provides preliminary evidence that neonatal thrombocytopenia incidence is high in infants born to mothers with immune thrombocytopenic purpura. This study further reports that the largest proportion of these cases are severe.